OWASP Framework and OCTAVE Method for Penetration Testing Web Apps of College X - Darmayuda, I Putu Gede Angga Mas; Sasmita, Gusti Made Arya; Putri, Gusti Agung Ayu (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2024)
Information system security is a major focus for many organizations as increasingly sophisticated cyberattacks threaten the confidentiality, integrity and availability of online services. This research aims to identify and assess vulnerabilities in web applications at College X by using the OWASP framework and OCTAVE method. OWASP is used to identify common and critical web vulnerabilities, while OCTAVE provides a holistic understanding of an organization's security risks. Testing was conducted with the tools and techniques recommended by both frameworks. The results found a number of vulnerabilities, including two low-level and one high-level. The findings underscore the importance of systematic penetration testing and risk assessment to keep web applications secure in educational environments.